Comparison of methods for estimating premorbid intelligence. Issue 1 (2nd January 2020) - Bright, Peter; van der Linde, Ian
ABSTRACT: To evaluate impact of neurological injury on cognitive performance it is typically necessary to derive a baseline (or "premorbid") estimate of a patient's general cognitive ability prior to the onset of impairment. In this paper, we consider a range of common methods for producing this estimate, including those based on current best performance, embedded "hold/no-hold" tests, demographic information, and word reading ability. Ninety-two neurologically healthy adult participants were assessed on the full Wechsler Adult Intelligence Scale – Fourth Edition (WAIS-IV; Wechsler, D. (2008). Wechsler Adult Intelligence Scale (4th ed.). San Antonio, TX: Pearson Assessment.) and on two widely used word reading tests: National Adult Reading Test (NART; Nelson, H. E. (1982). National Adult Reading Test ( NART ): For the assessment of premorbid intelligence in patients with dementia: Test manual . Windsor: NFER-Nelson.; Nelson, H. E., & Willison, J. (1991). National Adult Reading Test ( NART ). Windsor: NFER-Nelson.) and Wechsler Test of Adult Reading (WTAR; Wechsler, D. (2001). Wechsler Test of Adult Reading: WTAR . San Antonio, TX: Psychological Corporation.). Our findings indicate that reading tests provide the most reliable and precise estimates of WAIS-IV full-scale IQ, although the addition of demographic data provides modest improvement. Nevertheless, we observed considerable variability in correlations between NART/WTAR scores and individual WAIS-IV indices, which indicated particular usefulness in estimating more crystallised premorbid abilities (as represented by the verbal comprehension and general ability indices) relative to fluid abilities (working memory and perceptual reasoning indices). We discuss and encourage the development of new methods for improving premorbid estimates of cognitive abilities in neurological patients.